Berberine regulates AMP‐activated protein kinase signaling pathways and inhibits colon tumorigenesis in mice. Issue 10 (17th May 2014) - Li, Weidong; Hua, Baojin; Saud, Shakir M.; Lin, Hongsheng; Hou, Wei; Matter, Matthias S.; Jia, Libin; Colburn, Nancy H.; Young, Matthew R.
Abstract : Colorectal cancer, a leading cause of cancer death, has been linked to inflammation and obesity. Berberine, an isoquinoline alkaloid, possesses anti‐inflammatory, anti‐diabetes and anti‐tumor properties. In the azoxymethane initiated and dextran sulfate sodium (AOM/DSS) promoted colorectal carcinogenesis mouse model, berberine treated mice showed a 60% reduction in tumor number ( P  = 0.009), a 48% reduction in tumors <2 mm, ( P  = 0.05); 94% reduction in tumors 2–4 mm, ( P  = 0.001), and 100% reduction in tumors >4 mm ( P  = 0.02) compared to vehicle treated mice. Berberine also decreased AOM/DSS induced Ki‐67 and COX‐2 expression. In vitro analysis showed that in addition to its anti‐proliferation activity, berberine also induced apoptosis in colorectal cancer cell lines. Berberine activated AMP‐activated protein kinase (AMPK), a major regulator of metabolic pathways, and inhibited mammalian target of rapamycin (mTOR), a downstream target of AMPK. Furthermore, 4E‐binding protein‐1 and p70 ribosomal S6 kinases, downstream targets of mTOR, were down regulated by berberine treatment. Berberine did not affect Liver kinase B1 (LKB1) activity or the mitogen‐activated protein kinase pathway. Berberine inhibited Nuclear Factor kappa‐B (NF‐κB) activity, reduced the expression of cyclin D1 and survivin, induced phosphorylation of p53 and increased caspase‐3 cleavage in vitro. Berberine inhibition of mTOR activity and p53 phosphorylation was found to be AMPK dependent, while inhibition NF‐κB was AMPK independent. In vivo, berberine also activated AMPK, inhibited mTOR and p65 phosphorylation and activated caspase‐3 cleavage. Our data suggests that berberine suppresses colon epithelial proliferation and tumorigenesis via AMPK dependent inhibition of mTOR activity and AMPK independent inhibition of NF‐κB. © 2014 Wiley Periodicals, Inc.